2014
DOI: 10.3390/environments1020190
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Willingness to Pay for Household Kitchen Waste Separation Services in Haidian and Dongcheng Districts, Beijing City

Abstract: This paper reports a contingent valuation study on household kitchen waste separation (HKWS) services via willingness to pay (WTP) conducted in the Haidian and Dongcheng districts of Beijing city in 2013. This study focuses on a real program to understand households' attitudes toward HKWS and to estimate the value of HKWS services. The results of this study revealed that 41.4% agreed to accept the proposed price of HKWS services, while 42.2% refused to pay, but with a positive attitude toward the HKWS program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In other words, Chinese residents have not been habituated to separating KW. Therefore, this finding can be further explained by the results found by Yuan and Yabe [4]. In their study, residents who had higher positive attitudes towards household KW separation showed a higher willingness to pay for KW separation services.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…In other words, Chinese residents have not been habituated to separating KW. Therefore, this finding can be further explained by the results found by Yuan and Yabe [4]. In their study, residents who had higher positive attitudes towards household KW separation showed a higher willingness to pay for KW separation services.…”
Section: Discussionsupporting
confidence: 49%
“…In this respect, source separation by the generator has been widely recognized as the crucial way for reducing, reusing, and recycling waste [1][2][3][4][5][6][7][8]. Many researchers have identified means of how to successfully conduct source separation in developed countries, such as in Sweden by Dahlén et al [9], and in Spain by Gallardo et al [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WTP has been used in many waste retribution studies. Among them are WTP for waste sorting management improvement [19,20], WTP for repairment of waste processing construction [21], and WTP to undertake recycle program [22]. WTP in rural areas that have not been connected to electricity has been conducted by [23].…”
Section: Willingness To Paymentioning
confidence: 99%
“…For the purpose, WTP questionnaire was designed based on [20]. The questionnaire is divided into five parts.…”
Section: Willingness To Paymentioning
confidence: 99%